Pemetaan Kasus COVID-19 Menggunakan K-Means Clustering di Kota Padang Tahun 2020 - Siti Aisyah A Hutagalung; Endah Purwaningsih (JURNAL BUANA, 2022)
This study aims to (1) find out the results of clustering the spread of COVID-19 cases in the city of Padang using the K-Means method in 2020 (2) find out the Geographic Information System mapping the distribution of COVID-19 cases in the city of Padang in 2020 from the results of clustering. The research method used is quantitative research. Data collection is literature study. Data analysis technique used is the K-Means clustering method. Results of this study are (1) Produce 2 clusters with 7 sub-districts in the cluster (C1) vulnerable, namely Padang Utara Subdistrict, Lubuk Kilangan, Padang Barat, Pauh, Padang Selatan, Nanggalo and Bungus. Cluster (C2) is very vulnerable, there are 4 sub-districts, namely Padang Timur Subdistrict, Koto Tangah, Kuranji, and Lubuk Begalung. (2) GIS the results of the clustering can inform the public in the city of Padang where the sub-districts are vulnerable and extremely vulnerable to COVID-19.